Chronic Traumatic Encephalopathy: A Comparison with Alzheimer's Disease and Frontotemporal Dementia - Lesman-Segev, Orit H.; Edwards, Lauren; Rabinovici, Gil D. (Seminars in Neurology, 2020)
The clinical diagnosis of chronic traumatic encephalopathy (CTE) is challenging due to heterogeneous clinical presentations and overlap with other neurodegenerative dementias. Depending on the clinical presentation, the differential diagnosis of CTE includes Alzheimer's disease (AD), behavioral variant frontotemporal dementia (bvFTD), Parkinson's disease, amyotrophic lateral sclerosis, primary mood disorders, posttraumatic stress disorder, and psychotic disorders. The aim of this article is to compare the clinical aspects, genetics, fluid biomarkers, imaging, treatment, and pathology of CTE to those of AD and bvFTD. A detailed clinical evaluation, neurocognitive assessment, and structural brain imaging can inform the differential diagnosis, while molecular biomarkers can help exclude underlying AD pathology. Prospective studies that include clinicopathological correlations are needed to establish tools that can more accurately determine the cause of neuropsychiatric decline in patients at risk for CTE.
Keywords: chronic traumatic encephalopathy; differential diagnosis; Alzheimer's disease; frontotemporal dementia